Comprehensive investigation and prediction model for mechanical properties of coconut wood–polylactic acid composites filaments for FDM 3D printing - Kananathan, Jeeven; Samykano, Mahendran; Kadirgama, K.; Devarajan, Ramasamy; Rahman, Md Mustafizur
Fused deposition modeling (FDM) is a practical 3D printing technology to print thermoplastic and composite materials. The FDM 3D printing process has gained substantial attention due to its capability to produce complex and accurate components. Recently, the wood particles-based flament in 3D printing has become a subject of interest, which is due to their prominent advantages, such as thermal resistivity, corrosion resistivity, biodegradable characteristics, and being environmentally friendly. Therefore, this research study aims to investigate the mechanical properties and statistical prediction model development for coconut wood–polylactic acid (PLA). The experimental investigation was carried out according to the ASTM standards (tensile—ASTM D638 Type 1, compression—ASTM D695, and bending—ASTM D790) at diferent infll densities (25, 50, and 70%) and fve diferent infll patterns. The obtained results proved that concentric infll pattern accompanied by 75% infll percentage achieved the most outstanding tensile and bending behavior. For compression testing, grid infll pattern accompanied by 75% infll percentage exhibits maximum compression properties. In overall, the octagram spiral infll pattern shows the weakest properties among all the infll patterns. The experimental results were further analyzed using response surface methodology to identify the efectiveness of studied parameters on mechanical properties and to derive a mathematical model. The derived mathematical models related to studied mechanical properties have been proposed to predict the desired mechanical properties with respect to the variation of infll patterns and percentages.